Zebrafish as a Model for Fetal Alcohol Spectrum Disorders - Alsakran, Amena; Kudoh, Tetsuhiro (Frontiers in Pharmacology, 2021)
In this review, we will discuss zebrafish as a model for studying mechanisms of human fetal alcohol spectrum disorders (FASDs). We will overview the studies on FASDs so far and will discuss with specific focus on the mechanisms by which alcohol alters cell migration during the early embryogenesis including blastula, gastrula, and organogenesis stages which later cause morphological defects in the brain and other tissues. FASDs are caused by an elevated alcohol level in the pregnant mother’s body. The symptoms of FASDs include microcephaly, holoprosencephaly, craniofacial abnormalities, and cardiac defects with birth defect in severe cases, and in milder cases, the symptoms lead to developmental and learning disabilities. The transparent zebrafish embryo offers an ideal model system to investigate the genetic, cellular, and organismal responses to alcohol. In the zebrafish, the effects of alcohol were observed in many places during the embryo development from the stem cell gene expression at the blastula/gastrula stage, gastrulation cell movement, morphogenesis of the central nervous system, and neuronal development. The data revealed that ethanol suppresses convergence, extension, and epiboly cell movement at the gastrula stage and cause the failure of normal neural plate formation. Subsequently, other cell movements including neurulation, eye field morphogenesis, and neural crest migration are also suppressed, leading to the malformation of the brain and spinal cord, including microcephaly, cyclopia, spinal bifida, and craniofacial abnormalities. The testing cell migration in zebrafish would provide convenient biomarkers for the toxicity of alcohol and other related chemicals, and investigate the molecular link between the target signaling pathways, following brain development.